Identification of key candidate genes and marker metabolites of melanin synthesis in black-bone chicken - Ziyi Fang; Zhengxiao He; Weifang Yang; Yongli Wang; Yanji Chen; Lilin Men; Richun Cai; Yang Yu; Yaxiong Jia; Guiping Zhao (BMC Genomics)
Abstract Background Blackness and growth traits are regarded as crucial economic traits in black-bone chicken production. In order to meet consumers’ demand for black-bone chickens, it is necessary to study the mechanisms of body weight growth and melanin deposition in black-bone chickens. The genetic variations in growth traits, blackness traits, breast muscle transcriptome, and metabolism were compared between the Yanjin black-bone (YJ) chicken group (n = 20) and Jinling Partridge black-bone (JL) chicken group (n = 20). In addition, very high-melanin content (HB) individuals (n = 6) and very low-melanin content individuals (LB) (n = 6) were selected from the JL chicken group to investigate the melanin synthesis mechanism. Results Comparison between the breast muscle transcriptomes of YJ chickens and JL chickens, as well as between HB and LB of JL chickens, revealed that 81 common differentially expressed genes (DEGs) were significantly enriched in melanosomes, pigment particles, and melanogenesis pathways. Among them, four candidate genes, namely TYRP1, KIT, PRKCB and EDNRB2, may be significantly associated with melanin production in black-bone chicken breast muscle. Also, 2 of the marker metabolites among the 16 common differential metabolites (DMs) identified, namely tetrahydrobiopterin (BH4) and N-acetylneuraminic acid, significantly contribute to melanin synthesis in the breast muscle of black-bone chickens. Conclusion Our research presents complex regulatory networks of DEGs and DMs in melanin synthesis pathways. The results establish a basis for raising black-bone chickens with optimal melanin levels and offer a theoretical framework for investigating the mechanisms of melanin formation in these hens.